Preparation of Spinel Form Co3O4 and CoO2 Thin Film at Low Temperature by Electrochemical Method as a Thin Film Oxide Layer - Hacinecipoglu, Ayse, V; Gencten, Metin; Arvas, Melih B.; Sahin, Yucel (ELECTROCHEMICAL SOC INC, 2022)
In this work, thin films of cobalt oxides (CoO2, Co3O4) were prepared using the electrochemical method on the pencil graphite and indium tin oxide surfaces. The substrate effect in the production of both oxides has been studied in detail. While Co3O4 accumulates on the pencil graphite's surface, CoO2 formation was observed on the indium tin oxide. The characterization of the cobalt oxides was carried out using the X-ray diffraction, Atomic force microscope, and Scanning electron microscope. In this context, the cobalt oxide crystal structure in the range of (-1.0 V)-(+1.9 V) was synthesized on different substrates and at extremely low temperatures (20 degrees C to 25 degrees C), using the cyclic voltammetry method, which is a simple one-stage way. Calculated band gap value for ITO/CoO2 as 2.5 eV shows a potential use of this electrode in solar cell applications.
Keywords: LITHIUM-ION BATTERIES; COBALT OXIDE; CYCLIC VOLTAMMETRY; HYDROGEN-PEROXIDE; ELECTRODE; OXYGEN; NANOCOMPOSITES; NANOPARTICLES; CAPACITANCE; BEHAVIOR; Materials Science; Physics